News Notes. - Hendriksen, Eldon S. (The Accounting Review, 1971)
Abstract Presents news briefs related to accounting education as of October 1971. Retirement of E. Bryan Smyth from the University of New South Wales; List of accounting professors who joined the University of Florida; Appointment of Ralph J. Winston as a University Professor of Accounting at the Governors State University in Illinois.